Chemical analysis and survey of mycotoxins in South African produced grains with emphasis on those produced by stenocarpella maydis in maize - Maharaj, Vinesh J. (University of Pretoria, 2024)
Thesis (PhD (Chemistry))--University of Pretoria, 2024.